Rapid detection of pork and pig derivatives based on volatile compounds aroma using electronic nose - Ismarti Ismarti (Journal of Halal Product and Research)
The development of food processing technology has increased the number and types of food products to meet human needs. The quality of a food product is not only seen from nutritional value and safety, but also from halalness aspect. For the purposes of quality control and halal authentication, the existence of a food testing method that is fast, accurate and easy to handling is needed. The application of electronic nose for various volatile compound detection purposes has been widely reported. This paper discusses electronic nose applications for quality control and halal testing purposes on food products. Furthermore, it also discussed the advantages and disadvantages of testing with an electronic nose. Based on the discussion, the electronic nose is a portable detection tool that is user friendly, fast and accurate for the identification and detection of food products based on the presence of the aroma of volatile compounds in the material. The advantages of this electronic nose have the potential to be used as an alternative rapid detection instrument in food testing, especially in authenticating pork and pig derivative.